Acute and sub-chronic toxicological assessment of Nannochloropsis oculata in rats - Kafaie, Soroush; Loh, Su Peng; Mohtarrudin, Norhafizah (Academic Journals, 2012)
The aim of this study was to investigate the acute and sub-chronic toxicities of Nannochloropsis oculata biomass. In the acute toxicity study, twelve Sprague-Dawley rats of both sexes were gavaged with 12 g/kg body weight (bw) of N. oculata one time, and then tested for morbidity and mortality in 14 days. The oral LD50 of N. oculata in rats was greater than 12 g/kg bw, and no toxicity effects were observed on biomass in terms of morbidity signs, plasma biochemical parameters, organ tissue, or body weight gain in response to N. oculata doses up to 12 g/kg rat bw. In the sub-chronic toxicity study, thirty-six Sprague-Dawley rats of both sexes were chosen and divided into three groups and provided with a diet containing 0, 3, and 6 g of N. oculata per kg bw, respectively, early every morning and then allowed free access to normal food and water ad libitum for 60 days. No biologically significant effects of N. Oculata on organ weights, male body weight gain, or on the plasma biochemical parameters were observed in either treatment group. However, low creatinine and significant differences in body weight gain by female rats were noted in the treatment groups. These changes were not considered as toxicologically significant. The no observable adverse effect level (NOAEL) for N. Oculata under the conditions of this study was 12 g/kg bw/day for acute toxicity and 6 g/kg bw/day for sub-chronic toxicity for both male and female rats.